Análisis de factibilidad para la implementación de una infraestructura de almacenamiento NAS en la Clínica CETDOL de la ciudad de Guayaquil - Caicedo Monserrate, Juan Manuel (2021)
The purpose for which this project was carried out is to obtain a better storage of the information of the patients of the CETDOL clinic. For which the study was carried out and the necessary information was collected in order to obtain a clear idea about what needed to be satisfied, which was evidenced that the storage was manually or through the office and mail package of the aforementioned clinic . A descriptive case study was implemented in addition to the respective survey of engineers in the systems branch where they provided us with their knowledge about storages and the respective investigation of NAS storages, the types, characteristics and number of bays.